MENGHIDUPKAN KEMBALI KAWASAN STASIUN KAMPUNG BANDAN, JAKARTA UTARA DENGAN KONSEP KAWASAN BERORIENTASI TRANSIT - Clara Aurellia Djaja; Rudy Trisno (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The loss of image, existence, and mobility of Kampung Bandan Station, which has existed since the Dutch era, occurs due to the following: the difficulty of access to achievement; the surrounding environment being surrounded by slums caused by large-scale urbanization, in which these slums are also the cause of disasters such as floods and fires; the condition of the area that is not visible from the road and highways; as well as the vulnerability of criminal cases that can occur due to narrow, quiet, and dark areas. The purpose of this study is to revive the image, existence, and mobility of the Kampung Bandan Station area which was previously degraded to become alive again and have a positive effect on the surrounding environment. This research using the Urban Acupuncture and Deconstruction methods which obtained several research indicators; 1) Everydayness of the area around Kampung Bandan Station; 2) Implementation of Transit Oriented Development (TOD); 3) Building with Deconstruction method; 4) Application of the concept of sustainable design. The results of this project are presented as design indicators by developing a location that can improve the quality of life of the neighborhood while restoring the image, existence, and mobility of the Kampung Bandan Station area. Keywords:  Jakarta; Kampung Bandan Station; Poverty; Slums Abstrak Hilangnya citra, eksistensi, dan mobilitas Stasiun Kampung Bandan yang telah ada sejak zaman Belanda, dikarenakan sulitnya akses pencapaian; lingkungan sekitarnya yang dikelilingi oleh pemukiman kumuh yang disebabkan karena urbanisasi secara besar – besaran yang mana pemukiman kumuh ini juga menjadi penyebab terjadinya bencana seperti banjir dan kebakaran; kondisi kawasan yang tidak terlihat dari jalan raya; serta rawannya kasus kriminalitas yang dapat terjadi akibat area sempit, sepi, dan gelap. Tujuan dari penelitian ini adalah menghidupkan kembali citra, eksistensi, serta mobilitas kawasan Stasiun Kampung Bandan yang sebelumnya mengalami degradasi menjadi hidup kembali dan memberikan efek positif terhadap lingkungan di sekitarnya. Penelitian ini metode perancangan yang digunakan adalah deconstruction dengan beberapa aspek yaitu; 1) Everydayness kawasan sekitar Stasiun Kampung Bandan; 2) Penerapan Transit Oriented Development (TOD); 3) Bangunan dengan metode Deconstruction; 4) Penerapan konsep desain sustainability. Temuan dari proyek ini berupa indikator perancangan dengan diciptakannya sebuah tempat yang dapat mengembalikan citra, eksistensi, dan mobilitas di kawasan Stasiun Kampung Bandan serta meningkatkan kualitas hidup masyarakat di sekitarnya.